DEFINING AN AMERICAN MAN : A STUDY ON THE CON-STRUCTION OF AMERICAN MASCULINITY - JULIATI, M.Hum. (ISSN)
The image of an American man has come into an important discussion since the eighteenth century. The characters exposed in literary works and visual media have created the images what the American man is supposed to be like.  In fact, the concept of what the American should be like has been through some changes along with the historical records of The United States. This study used social construction theory to elaborate how the idea is constructed. The study found out the contribution of social, economic, cultural, and political aspects to the idea of what the American man is like.